BROODSTOCK FECUNDITY AND FRY SURVIVABILITY IN NILE TILAPIA (Oreochromis niloticus): EFFECTS OF DIETARY NUCLEOTIDE SUPPLEMENTATION IN AN ON-FARM FEEDING TRIAL (Proceedings International Conference on Fisheries and Aquaculture, 2025)
The rapid expansion of global aquaculture has highlighted the importance of optimizing tilapia broodstock management to address challenges such as low fecundity and fry survival. This study explores the potential of dietary nucleotide supplementation, specifically Nucleoforce Aqua™, in enhancing broodstock fecundity and fry survival within tilapia aquaculture systems. A farm feeding trial, adapted to the principles of practical farm practice, involved administering dietary nucleotides at a 0.05% concentration to tilapia broodstock over a span of thirty (30) days, with the experiment encompassing two distinct treatment groups: T1, supplemented with dietary nucleotides, and T2, a control group without supplementation. Preliminary findings unveil promising trends. Broodstock receiving Dietary Nucleotide exhibited significantly higher fry production and survival rates compared to the control. Analysis of O. niloticus fecundity underscores a marked disparity between treatments. T1 yielded an average of 186,000 fry, outperforming T2's 124,000 fry produced from Commercial Diet alone. The Independent Samples T-Test confirmed the statistical significance of this difference, with p-values of 0.004 (one-tailed) and 0.008 (two-tailed), both below the standard significance threshold of 0.05. This result indicates a statistically significant effect of dietary nucleotide supplementation on fecundity. Although fry survival rates between T1 (65%) and T2 (62%) showed minimal differences, the marked 50% increase in fecundity underscores the potential of nucleotide supplementation to enhance reproductive outcomes. These findings suggest that dietary nucleotides can enhance broodstock productivity, addressing challenges in tilapia aquaculture and potentially improving farm sustainability and profitability. This study contributes to the understanding of nutritional strategies in improving broodstock performance and overall aquaculture productivity. Further research is recommended to explore the effects of nucleotide supplementation under varied environmental conditions and to assess cost-effectiveness, enabling the optimization of this technology for broader application in the industry.
Keywords: sustainability; aquaculture; nucleotide supplimentation; broodstock management; fecundity; Tilapia fry survival